Women Economic Empowerment Study - World Bank (World Bank, Washington, DC, 2019)
The Women Economic Empowerment report outlines the factors contributing to the persistently low economic participation of Egyptian women and to identify "gender smart" policies and solutions to boost economic growth while at the same time, narrowing relevant gender gaps. The study provides the context of women's share of the public space as reflected in their access to education, health, social protection, and decent work opportunities. It provides qualitative insights into women's perceptions regarding working conditions and challenges, including the reconciliation between work and marriage, and the relation between household responsibilities, earnings, and the dynamics of decision making in the household. It also discusses the various gender conscious and unconscious biases affecting women's work in the private sector while providing recommendations to promote gender diversity in the workplace, and boosting the inclusion of women, particularly in leadership positions. Lastly, it identifies the top 12 industries where women's work is concentrated and/or promising by providing an analysis of the characteristics of the female labor force in these industries.